Innovation in Citizen Science – Perspectives on Science-Policy Advances. (27th April 2018) - Hecker, Susanne; Bonney, Rick; Haklay, Muki; Hölker, Franz; Hofer, Heribert; Goebel, Claudia; Gold, Margaret; Makuch, Zen; Ponti, Marisa; Richter, Anett; Robinson, Lucy; Iglesias, Jose Rubio; et al.
Citizen science is growing as a field of research with contributions from diverse disciplines, promoting innovation in science, society, and policy. Inter- and transdisciplinary discussions and critical analyses are needed to use the current momentum to evaluate, demonstrate, and build on the advances that have been made in the past few years. This paper synthesizes results of discussions at the first international citizen science conference of the European Citizen Science Association (ECSA ) in 2016 in Berlin, Germany, and distills major points of the discourse into key recommendations. To enhance innovation in science, citizen science needs to clearly demonstrate its scientific benefit, branch out across disciplines, and foster active networking and new formats of collaboration, including true co-design with participants. For fostering policy advances, it is important to embrace opportunities for policy-relevant monitoring and policy development and to work with science funders to find adequate avenues and evaluation tools to support citizen science. From a society angle it is crucial to engage with societal actors in various formats that suit participants and to evaluate two-way learning outcomes as well as to develop the transformative role of science communication. We hope that these key perspectives will promote citizen science progress at the science-society-policy interface.